Penerapan Internet of Things Pada Sistem Kendali Pengisian Token Listrik Prabayar - Lesmideyarti, Dwi; Rachman, Fathur Zaini; Ihsan, Ihsan (JST (Jurnal Sains Terapan), 2024)
Filling in electricity tokens is very important for the continued use of electricity, be it filling up prepaid Kwh electricity tokens so that the need for automatic filling is urgently needed to reduce difficulties in filling in electricity tokens manually. In designing an Internet of Things (IoT) based system that is designed to provide automatic charging control remotely, using the ESP32 microcontroller, ESP32 CAM, and other components, this system can monitor the condition of the electricity meter and send notifications to smartphones when the pulse is nearing exhaustion. Furthermore, with the relay module, the system automatically enters the token code via a push pull solenoid. The test results show that this system can provide notifications with an average time of 41 seconds and sending messages for 43 seconds. ESP32-CAM sends data to a smartphone with a delay in sending messages and photos on Telegram, with the fastest speed of 2 seconds, sending messages for 3 seconds, and sending photos on average 6.2 seconds, from the results obtained that the tool that has been designed can provide increased comfort and efficiency for the user when the user is not at the Kwh of electricity location when the electricity token runs out soon.Keywords: Internet of Things, Sensor, Relay, Microcontroller